Socioeconomic Inequality and Judicial Disparities In Drug Sentencing: A Mixed-Methods Study on Rehabilitation vs Imprisonment In Indonesia - Kasmanto Rinaldi; Heni Susanti; Suyatno Ladiqi; Dita Fisdian Adni (Universitas Muhammadiyah Bandung, 2026)
Drug-related arrests in Indonesia frequently result in disparate legal outcomes influenced by extralegal determinants, raising concerns about fairness and consistency within the national drug policy framework. This study examines the factors shaping judicial decisions between rehabilitation and imprisonment within the Indonesian legal system. Employing a mixed-methods design, the research integrates quantitative analysis of secondary data derived from judicial decisions and reports of the National Narcotics Agency (BNN) covering the period 2019–2024, with qualitative insights obtained through in-depth interviews, analyzed using NVivo 12. The analysis is grounded in critical criminology and Islamic legal principles, particularly maqāṣid al-sharī‘ah. Within this framework, “systemic bias” is operationalized as patterned disparities in sentencing outcomes associated with extralegal factors, including socioeconomic status and drug type. The findings indicate that individuals from lower socioeconomic backgrounds and those involved with synthetic drugs are significantly more likely to receive custodial sentences, whereas defendants from higher socioeconomic groups or associated with traditional substances are more frequently directed toward rehabilitation programs. These disparities reflect structural inequalities that undermine both legal rationality and the normative objectives of justice, including the protection of life, intellect, and social welfare as emphasized in maqāṣid al-sharī‘ah. To address these issues, the study advocates for comprehensive legal reforms, including the standardization of sentencing guidelines, expanded access to rehabilitation services, strengthened inter-agency coordination, and a shift toward a harm-reduction approach to promote a more equitable system of drug law enforcement in Indonesia.